2017
DOI: 10.1017/s1355617717000583
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Correlations of Visuospatial and Visuoperceptual Tests in Parkinson’s Disease

Abstract: Background: Diagnosis of mild cognitive impairment in Parkinson’s disease (PD) is relevant because it is a marker for evolution to dementia. However, the selection of suitable tests to evaluate separate cognitive domains in mild cognitive impairment related to PD remains an open question. The current work aims to investigate the neuroanatomical correlates of several visuospatial/visuoperceptual tests using the same sample and a multimodal MRI approach. Methods: The study included 36 PD patients and 20 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…In our previous cross-sectional studies, we demonstrated a relationship between visuospatial and visuoperceptual performance and cortical thickness in bilateral temporo-parietaloccipital areas, and widespread posterior-anterior white matter microstructure alterations [13,14]. Interestingly, in the present study, we have established a relationship between the progressive worsening in VS/VP performance and bilateral degeneration of posterior cortical regions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In our previous cross-sectional studies, we demonstrated a relationship between visuospatial and visuoperceptual performance and cortical thickness in bilateral temporo-parietaloccipital areas, and widespread posterior-anterior white matter microstructure alterations [13,14]. Interestingly, in the present study, we have established a relationship between the progressive worsening in VS/VP performance and bilateral degeneration of posterior cortical regions.…”
Section: Discussionsupporting
confidence: 76%
“…Several cross-sectional structural MRI correlational studies have established a relationship between the degeneration of posterior brain regions and cognitive impairment [9e12]. Specifically, previous studies by our group showed that visuospatial and visuoperceptual (VS/VP) tests are suitable to reflect cortical thinning in lateral temporo-parietal regions in PD patients [13,14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of the 45 publications, which met inclusion criteria, one article was a review but not a systematic review, which is not included in the table, 30 articles proposed discrete lesion locations in the brain related to the CDT summarized in Table and Figure 2 . Nine articles examined the degree of white matter burden related to CDT (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Pattern 2 patients showed impaired performance in HVLT-R total learning, delayed recall, Symbol Digits Modalities Test, and MoCA. Impairment in total learning and delayed recall have been found to be good markers of future cognitive deterioration in PD [23], and the Symbol Digits Modalities Test is a suitable marker of cortical thinning in lateral temporo-parietal regions [24]. Posterior cortical-based neuropsychological deficits have been related to higher risk of evolution to dementia [25].…”
Section: Discussionmentioning
confidence: 99%